2024
DOI: 10.1039/d3tb02346j
|View full text |Cite
|
Sign up to set email alerts
|

Dual role far red fluorescent molecular rotor for decoding the plasma membrane and mitochondrial viscosity

Akshay Silswal,
Anup Pramanik,
Apurba Lal Koner

Abstract: Rationally designed Julolidine-based molecular rotor (JMT) targets mitochondria with far-red emission accounting for mitochondrial dysfunction. Further, the communication between mitochondria and plasma membrane was investigated upon mitochondrial depolarization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…As shown in Figure d–g, both of the merged channels showed an excellent overlap, further demonstrating the organelles (mitochondria and nucleolus) targeted by SYN before and after mitochondrial damage. In addition, due to the presence of a high-viscosity environment in the mitochondrial matrix and nucleolus, the rotor effect in SYN gives it good imaging quality for mitochondria and nucleolus. , After irradiation, the localization of SYN for other organelles (such as lysosome and endoplasmic reticulum) was also inspected using commercial dyes (Figure S9), the poor overlap of SYN and the commercial dyes indicated that SYN did not target other organelles. Additionally, images of live HeLa cells that were irradiated discontinuously and stained with SYN were obtained, as shown in Figure S10.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure d–g, both of the merged channels showed an excellent overlap, further demonstrating the organelles (mitochondria and nucleolus) targeted by SYN before and after mitochondrial damage. In addition, due to the presence of a high-viscosity environment in the mitochondrial matrix and nucleolus, the rotor effect in SYN gives it good imaging quality for mitochondria and nucleolus. , After irradiation, the localization of SYN for other organelles (such as lysosome and endoplasmic reticulum) was also inspected using commercial dyes (Figure S9), the poor overlap of SYN and the commercial dyes indicated that SYN did not target other organelles. Additionally, images of live HeLa cells that were irradiated discontinuously and stained with SYN were obtained, as shown in Figure S10.…”
Section: Resultsmentioning
confidence: 99%
“…In another variation, we modified the rotor by introducing a trimethyl ammonium cationic group, guiding the resulting JMT rotor to the mitochondria of cells. 38 JMT was then utilized to assess mitochondrial stress, leveraging the fact that under stress conditions, the viscosity of mitochondria tends to increase. Researchers have documented a distinct form of cell death called ferroptosis, which is dependent on iron and differs in appearance and biochemical characteristics from apoptosis, necrosis, and autophagy.…”
Section: Applications Of Julolidine-based Fmrsmentioning
confidence: 99%